Pendampingan Akreditasi Jurnal Nasional (Arjuna) Ta’diban Sekolah Tinggi Ilmu Tarbiyah Hidayatullah Batam - Muthma'innah Muthma'innah; Syamsidah Lubis; Sari Mahwati Hasibuan; Saidah Oktariyati (LPPM-IAI Hidayatullah Batam, 2026)
National journal accreditation is one of the eligibility criteria that shows a journal can be accredited or recognized nationally. STIT Hidayatullah Batam strives to provide accreditation assistance for national journals, specifically the journal of the Elementary Madrasah Teacher Education Study Program (PGMI), namely the journal Ta'diban: Journal of Islamic Education. This community service aims to understand the process of accreditation assistance for national journals on Ta'diban: Journal of Islamic Education. The method used is the Participation Action Research (PAR) method. The results of the community service show that the assistance is carried out by analyzing the obstacles and shortcomings of the Ta'diban Journal. Furthermore, assistance is provided in the process of improving the Ta'diban Journal until it is successful in submitting the National Journal Accreditation application.